Le cercle et la droite, figures de la Consolation de Philosophie de Boèce - Bouton-Touboulic, Anne-Isabelle (Revue d'études augustiniennes et patristiques, 2011)
Based on the interest of Boethius for geometry, this article aims to explore the presence and signification of the circle and straight line figures in the Consolatio Philosophiae. The study of these figures makes it possible to recount how one moves from the deteriorated representations of the circle and the straight line to the geometric figures which are more and more purified-from the wheel of Fortune to the circles whose Providence is the centre, in a process where the neoplatonic interpretation of the Timaeus plays an important role. This path corresponds to the progress that Boethius, the prisoner, accomplished under the direction of Philosophy; however these figures also refer to the art of dialectic speech employed by the latter, which alternates linear and circular sequences of reasoning.